Sea Route Monitoring System Using Wireless Sensor Network Based on the Data Compression Algorithm - Li, Yang; Zhang, Zhongshan; Huangfu, Wei; Chai, Xiaomeng; Zhu, Xinpeng; Zhu, Hongliang (China communications, 2014)
The wireless sensor network （WSN） plays an important role in monitoring the environment near the harbor in order to make the ships nearby out of dangers and to optimize the utilization of limited sea routes. Based on the historical data collected by the buoys with sensing capacities, a novel data compression algorithm called adaptive time piecewise constant vector quantization （ATPCVQ） is proposed to utilize the principal components. The proposed system is capable of lowering the budget of wireless communication and enhancing the lifetime of sensor nodes subject to the constrain of data precision. Furthermore, the proposed algorithm is verified by using the practical data in Qinhuangdao Port of China.